2022
DOI: 10.1101/2022.09.11.507407
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Subjective assessment and taste strips testing of gustatory function, at home, and in the lab

Abstract: Gustatory ability is an important marker of health status, including COVID-19 disease. We compare self-reporting with home and lab psychophysical "taste strips" tests in healthy subjects. The taste test consisted of paper strips impregnated with sweet, bitter, salty, or sour tastants, and with the trigeminal stimulus capsaicin, each in high and in low concentration. The test was carried out either in a controlled lab environment (74 participants, 47 women) with the strips being administered by the experimenter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
1
0
0
Order By: Relevance
“…These self-reported ratings distinguished well between the two groups. These data are in accordance with previous studies that showed a positive relationship between subjects’ self-assessment and taste identification performance [ 41 , 42 ], whereas some other studies have not found this correlation on patients [ 43 , 44 , 45 , 46 ] or healthy subjects [ 47 ]. This divergence may be due to a common mistake in discrimination between decreased taste and retronasal olfaction [ 1 ], thus some patients who complain taste loss might not respond accurately to this type of questionnaire.…”
Section: Discussionsupporting
confidence: 93%
“…These self-reported ratings distinguished well between the two groups. These data are in accordance with previous studies that showed a positive relationship between subjects’ self-assessment and taste identification performance [ 41 , 42 ], whereas some other studies have not found this correlation on patients [ 43 , 44 , 45 , 46 ] or healthy subjects [ 47 ]. This divergence may be due to a common mistake in discrimination between decreased taste and retronasal olfaction [ 1 ], thus some patients who complain taste loss might not respond accurately to this type of questionnaire.…”
Section: Discussionsupporting
confidence: 93%